Bink & Gollie, best friends forever - DiCamillo, Kate (DiCamillo, Kate. Bink & Gollie., 2013)
Bink and Gollie's friendship remains strong, even in the face of Gollie's "royal blood," Bink's Stretch-O-Matic machine, and the pursuit of a world record.